The Southern Annular Mode: Variability, trends, and climate impacts across the Southern Hemisphere. (19th May 2020) - Fogt, Ryan L.; Marshall, Gareth J.
Abstract: The Southern Annular Mode (SAM) is the leading mode of extratropical Southern Hemisphere climate variability, associated with changes in the strength and position of the polar jet around Antarctica. This variability in the polar jet drives large fluctuations in the Southern Hemisphere climate, from the lower stratosphere into the troposphere, and stretching from the midlatitudes across the Southern Ocean to Antarctica. Notably, the SAM index has displayed marked positive trends in the austral summer season (stronger and poleward shifted westerlies), associated with stratospheric ozone loss. Historical reconstructions demonstrate that these recent positive SAM index values are unprecedented in the last millennia, and fall outside the range of natural climate variability. Despite these advances in the understanding of the SAM behavior, several areas of active research are identified that highlight gaps in our present knowledge. This article is categorized under: Paleoclimates and Current Trends > Earth System Behavior Abstract : The Southern Annular Mode has displayed an unprecedented positive polarity in the last several decades, with implications for climate across the entire extratropical Southern Hemisphere.